Human Amniotic Fluid Stem Cells Exert Immunosuppressive Effects on T Lymphocytes in Allergic Rhinitis - Zong, Ling; Wang, De; Long, Yanbo; Liu, Xiaolan; Tao, Ailin; Zhang, Lanzhen; Zhai, Jinming (Current Stem Cell Research & Therapy, 2023)
Aim: The study aims to investigate the immunomodulatory effect of Amniotic fluid stem (AFS) cells to Th2-skewed allergic rhinitis (AR) on T-lymphocyte proliferation, viability, activation and cytokine production. Background: AFS cells can suppress peripheral blood mononuclear cells (PBMCs) proliferation and display immunomodulatory properties, but AFS cells' immunoregulation on AR has not been defined. Methods: Human AFS cells were derived from magnetic cell sorting and co-cultured with PBMCs from AR patients stimulated by phytohemagglutinin (PHA). The AFS cells-associated suppressive proliferation was analyzed using CellTrace™ Violet assay; the T lymphocytes proliferation, viability, activation and the Foxp3+ Treg cells were determined by flow cytometry; cytokine levels were measured using an enzyme- linked immunosorbent assay. Results: We determined that AFS cells significantly inhibited PHA-induced CD3+ T lymphocyte proliferation at the ratio higher than 1:50 (AFS cells: PBMCs) (P<0.05); AFS cells obviously increased the T lymphocytes viability (P<0.01), inhibited the apoptosis of T lymphocytes (P<0.001), compared to PBMCs alone; AFS cells suppressed CD3+CD25+ T lymphocytes activated by PHA (P<0.05); AFS cells significantly promote Treg cells expansion in house dust mite (HDM)-stimulated PBMCs from AR patients (P<0.05). Compared with HDM-stimulated PBMCs, AFS cell co-culture predominantly decreased IL-4 level (P<0.05), but increased IFN-γ and IL-10 levels (P<0.01). Conclusion: AFS cells modulate the T-cells' immune imbalance towards Th2 suppression in AR, which can be used as a new cell banking for allergic airway diseases.
Keywords: Mesenchymal stem cells